Disrupted female estrous cyclicity in the intrahippocampal kainic acid mouse model of temporal lobe epilepsy. Issue 1 (5th December 2016) - Li, Jiang; Kim, Jae Seong; Abejuela, Vincent A.; Lamano, Jason B.; Klein, Natalie J.; Christian, Catherine A.
Summary: Objective: Reproductive dysfunction is a comorbidity that commonly occurs with temporal lobe epilepsy (TLE). Characterization of this comorbidity in various models of TLE in mice will greatly facilitate mechanistic investigations of the relationship between reproductive disorders and seizures initiated in the hippocampus. Here we investigate the impact on female reproductive estrous cyclicity in the intrahippocampal kainic acid mouse model of TLE and demonstrate the utility of using this model for future mechanistic studies. Methods: Kainic acid (KA) or saline vehicle was stereotaxically injected in the right dorsal hippocampus of adult female C57BL/6J mice. Development of epilepsy was assessed by video monitoring for behavioral seizures. Reproductive function was assessed by daily estrous cycle monitoring and ovarian morphology. Estrous cycles were monitored for up to 2 months after injection. Ovarian morphology was examined by histological staining and assessment of follicular and luteal development. Results: We observed spontaneous behavioral seizures in 82% of kainic‐acid‐treated mice. Irregular estrous cycles developed within 2 months after kainic acid injection. Sixty‐seven percent of KA‐treated mice showed disrupted estrous cycles, typically characterized by increased estrous cycle length, increased time spent in diestrus (nonfertile stage), and decreased time spent in estrus by 42 days post‐KA injection. The estrous cycle disruption, however, was not accompanied by major changes in ovarian morphology or follicular development. KA‐treated mice also displayed increased weight gain compared to control mice. Significance: These data indicate that comorbid female irregular estrous cyclicity arises in the intrahippocampal kainic acid mouse model of TLE. This is the first demonstration of disrupted reproductive endocrine function in a mouse model of TLE initially produced by an insult specifically targeted to the hippocampus. This model should thus be useful for basic studies investigating the neural mechanisms driving comorbid reproductive dysfunction in epilepsy in women.